(untitled) (Fiep Bulletin - online, 2025)
The aim of this study was to promote a theoretical reflection on human praxis by offering a new conceptualization and critical analysis of human movement, based on the science of human motricity and the thoughts of authors who are experts on the subject, verified in all the stages of processing this research. The qualitative result of the study is confirmed in the formulation of the executive-theoretical-practical archetype of motor behavior visualized in the structural organization chart created, punctuating the theoretical concept of all the integral and participatory components of this complex textual gear of motor action, developed and sustained on the severe phenomenological interpretation of all these prolegomena cited in the Motor Praxis that leads to an integrated and totalizing understanding of human movement and its intentionality.